ICT Use, Competitive Pressures, and Firm Performance in Mexico - Iacovone, Leonardo; Pereira-Lopez, Mariana; Schiffbauer, Marc (Published by Oxford University Press on behalf of the World Bank, 2019)
In this paper the authors present a set of stylized facts regarding the relation between information and communication technologies (ICT) use, firm performance, and competition. Taking advantage of a novel firm-level data set regarding ICT for Mexico, the authors find that firms facing higher competition appear to be the ones that have more incentives to increase their use of ICT. Accordingly, even though there is indeed a positive relation between ICT use and firm performance, this effect is greater for firms that face higher competition pressures, which is consistent with the theoretical predictions of the trade-induced technical change hypothesis.